The Pareto sales network asset: a networked power perspective - Augusty Tae Ferdinand; Maklon Felipus Killa (Business: Theory and Practice, 2018)
The purpose of this research is to develop a conceptual model dealing the relationship between EO and sales growth performance by proposing the Pareto sales network asset as a reliable bridge for mediating EO and sales growth performance in SMEs in Indonesia. Lending the network theory and the Pareto concept, we propose a concept on The Pareto sales network asset as a strategic asset for enhancing sales growth performance. The main finding of this study is that an entrepreneurial oriented firm who success in accessing the Pareto sales network which by nature is outside of the firm will get the networked power. Having, maintaining and using the networked power getting from a Pareto sales network asset will be a key asset for enhancing sales growth performance. The acceptance of the hypotheses on the role of the Pareto sales network asset demonstrated the importance of this strategic asset for SMEs in enhancing performance.